The Implementation of Referendum as a Limitation to Autocratic Legalism in the Formation of the Nusantara Capital City Law - Mahardika, Ahmad Gelora (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study employs a normative legal research method to analyze the rule of law, legal doctrines, and principles related to the implementation of referendums as limitations on legislative authority. Using a statutory approach, the research examines relevant Indonesian legislation, including the 1945 Constitution, Law Number 12 of 2011 on the Formation of Legislation, and the IKN Law. Primary legal materials, such as key statutes, and secondary legal materials, including academic literature, form the basis of the analysis. The study also incorporates comparative insights from South Korea's Constitutional Court decision on capital relocation. Findings reveal that referendums, while essential to participatory democracy, have been marginalized in Indonesia following the repeal of referendum provisions. Furthermore, the study critiques the legislative process of the IKN Law, highlighting its limited public participation and potential indicators of autocratic legalism. By analyzing compliance with democratic principles and the rule of law, the study identifies critical issues, such as co-optation of legislative power, constitutional violations, and compromised judicial independence, emphasizing the need for robust safeguards to prevent authoritarian tendencies in democratic systems. This research contributes to understanding the intersection of legal frameworks, public participation, and governance in Indonesia and beyond.